2007
DOI: 10.1111/j.1365-2486.2007.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and biological trait differences of stream macroinvertebrate communities between mediterranean and temperate regions: implications for future climatic scenarios

Abstract: Streams in mediterranean regions have highly seasonal discharge patterns, with predictable torrential floods and severe droughts. In contrast, discharge is less variable in temperate regions and intermittent flow conditions are uncommon. Hydroclimatic models predict that climate change would increase frequency and severity of floods and droughts across Europe, thus increasing the proportion of streams with mediterranean characteristics in actually temperate areas. Correspondingly, understanding actual ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
310
2
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(349 citation statements)
references
References 91 publications
12
310
2
12
Order By: Relevance
“…The effects of the ongoing global warming can be observed in many terrestrial, freshwater and marine species that have shifted their geographic ranges, seasonal activities, migration patterns, abundances, and species interactions, namely: freshwater fishes (Regier and Meisner, 1990), plants (Araujo et al, 2004;Lemieux and Scott, 2005), mammals (Burns et al, 2003), small birds (Wilby and Perry, 2006), and macroinvertebrates (Bonada et al, 2007). According to McLaughlin et al (2002) as well as to Pounds et al (2006), these changes in climate may have already caused several species extinctions.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the ongoing global warming can be observed in many terrestrial, freshwater and marine species that have shifted their geographic ranges, seasonal activities, migration patterns, abundances, and species interactions, namely: freshwater fishes (Regier and Meisner, 1990), plants (Araujo et al, 2004;Lemieux and Scott, 2005), mammals (Burns et al, 2003), small birds (Wilby and Perry, 2006), and macroinvertebrates (Bonada et al, 2007). According to McLaughlin et al (2002) as well as to Pounds et al (2006), these changes in climate may have already caused several species extinctions.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of temperature and precipitation regimes have the potential to have detrimental (or beneficial) effects and cause synergistic or antagonistic effects on species and communities [1]. Expected changes vary between cold, temperate and warm ecoregions, and could affect species due to changes in, among others, temperature, flow patterns, and nutrient concentrations [2][3][4][5]. However, estimates of effects from such changes on stream bioassessment results are rare.…”
Section: Introductionmentioning
confidence: 99%
“…For fish, the Fish Region Index (FRI, or Fish Zone Index) describes each fish species' preferred niche along the longitudinal upstream-downstream gradient [17] (Table 1). These ecological traits have been shown to mirror changes in fish communities due to climate change through a change in fish regions [17][18][19] and are also suggested in invertebrate communities [4,5,20]. Pletterbauer et al [17] showed mean increases of the Fish Zone Index between 0.25 and 0.41 up to the 2080s and maximum values of 0.92 and 1.18 under three climate change scenarios as developed by the Intergovernmental Panel on Climate Change (IPCC).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown a strong relationship between streamflow reductions and benthic response in Mediterranean-climate streams (Bonada et al, 2006(Bonada et al, , 2007aTorne´s et al, 2007;Morais, 2008). Furthermore, prolonged drought in Mediterranean-climate regions has particularly strong effects on the abundance and composition of benthic-macroinvertebrate communities in small streams (Beˆche et al, 2006;Beˆche and Resh, 2007a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The biological traits for a given taxon may include, for example, the number of generations per year, the ability to enter a state of diapause, and the ability to burrow into the streambed to obtain food, seek refuge from predators, or escape low-flow conditions (Beˆche and Resh, 2007a, b). Biological traits of benthic-macroinvertebrate communities in Mediterranean-climate regions have been shown to be affected by long-term climate variability (Beˆche et al, 2006;Beˆche and Resh, 2007a, b;Bonada et al, 2007a, b;Lawrence et al, 2010) and seasonal differences (Mouthon and Daufresne, 2006;Cordellier and Pfenninger, 2008;Spooner and Vaughn, 2008;Clausnitzer et al, 2009;Hering et al, 2009).…”
Section: Introductionmentioning
confidence: 99%